(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Coxsackie viruses belong to the Enterovirus genus and are commonly associated with mild, self-limiting infections. However, in certain cases particularly among neonates, young children, and immunocompromised individuals these infections may result in rare but potentially life-threatening complications. This article reviews the clinical characteristics of Coxsackie virus types A and B, transmission pathways, and severe complications including myocarditis, meningitis, encephalitis, pancreatitis, hepatitis, and serious neonatal infections. The aim of the study is to highlight the clinical significance of these complications and emphasize the importance of early diagnosis and careful monitoring in high-risk populations.